A German Hero for the Cold War: Wolfgang F. Henschel's Alpha Alpha (1972). - Hantke, Steffen (Science Fiction Studies, 2012)
Overlooked by critics of science fiction and historians of West German television, Wolfgang F. Henschel's series Alpha Alpha brought together elements of science fiction and the spy thriller, two genres imported largely from the U.S. that dominated the West German television landscape. Reproducing this hybrid genre in a national register provided writer and director Henschel with the opportunity to depart from the stereotypical settings, characters, and plot lines. Using science fiction to access and interrogate the spy thriller, Henschel attempted to transcend and challenge the rigid binaries organizing Cold War politics. The series' benign humanitarian postulate of individual ethical integrity overriding systemic technocratic and bureaucratic power makes the series symptomatic of a 1970s shift in German attitudes toward the U.S. in the wake of radical student protests against American foreign policy.